Educational Attainment and the Rural--Urban Divide in China. - Knight, J; Li, S (1996)
A national household income survey and census data are used to examine the determinants of educational attainment in China. Rural and Urban areas are analyzed separately, and contrasted, owing to the sharp economic and institutional divide between them. The roles of income, age, gender, ethnicity, region and family background are explored. An attempt is made to distinguish between demand-and supply-constraints. The opportunity and other costs of rural schooling, and the reasons for leaving school, are examined. Income levels and incentives are important in explaining rural dropping-out, and parental education is a powerful influence on enrollment and achievement. The considerable inequality of educational opportunity in China requires corrective policies.